The Social and Local Construction of Human Rights. Reflections from the Perspective of the Right to Education in Mexico - Zertuche Cobos, Víctor Alfonzo (2018)
The present article constitutes a critical reflection on human rights from the social-legal field in Mexico. Its purpose is to provide a discussion on a current legal and institutional reality, that is, the right to education in human rights based on one of the most important constitutional reforms in recent years in the field of human rights: the reform of June 2011. This reform, by the article 1° and 3° of the Constitution, introduced a public policy (proposed to the National Development Plan 2013-2018, along with the National Human Rights Program 2014-2018 within the federal public administration) whose object is to implement the teaching of human rights at the national level. In this proposal, we observe two effects, one positive and one negative, inscribed only in the institutional or official dimension of the Mexican State, from which is derived a third positive effect for the social or local sphere, that is to say, for the space where the popular sectors or cultural minorities live. Therefore, it is in this social or local sphere where the third positive effect of the national public policy would take place to rethink the counter-hegemonic and alternative use of the right to education in human rights, from where would be possible the social-local construction or reconstruction of human rights that the present and future society requires with some urgency.